Experimental study on wear failure of spindle hook teeth of cotton picker - Wang, Yugang; Li, Zhantao; Gu, Yanqing; Zhang, Hongwen; Zhao, Pengda; Wang, Yongzheng; Yang, Jianning (Frontiers in Materials, 2024)
I have improved the questions raised by the reviewers and marked the red fonts mainly including :1.For reviewer 1 and reviewer 2 : the error of hardness test is supplemented in the manuscript.2.Aiming at the first point of reviewer 2 : some writing errors in the text were modified, including capitalization, extra space and spelling errors.3.For the second point of reviewer 2 : already on Fig. 2 was modified.4.For the third point of reviewer 2 : my explanation is that Xinjiang is dry and dusty, and hard particles are the main form of wear. In the process of cotton harvesting, the closer to the root of the plant, the more hard particles such as sand and dust, and the farther away from the root of the plant, the less hard particles such as sand and dust, resulting in different degrees of wear at different positions of the spindle.Thank you very much for your suggestions. If there are other problems, please contact me in time.Yours,